Pengaruh Media Loto Warna dan Bentuk Terhadap Pemahaman Geometri Anak Kelompok B TK Dharma Wanita - Ratna Nila Puspitasari (Universitas Trunojoyo Madura, 2016)
The research on child group B in TK Dharma Wanita Bulukidul Village, Balong Ponorogo Subdistrict, was motivated by low understanding of geometry. This is seen from 10 of children have not been able to distinguish geometric shapes, explain geometric features, and have not been able to show geometry. This research uses quantitative research approach with pre-experimental design type and one-group research design pre test-post test design. Research subjects amounted to 20 children. Methods of data collection using observation by means of assessment in the form of observation sheet. Data analysis using non-parametric statistics Wilcoxon signed test (wilcoxon match pairs test) with the formula t arithmetic t table. Based on the results of data analysis of rough motor skills jumped two feet at the time of preliminary observation (pre test) and observation after treatment (post test) using traditional game of rubberan obtained average value of pre test result 11,6 and average result of post test 1 , 75. The result of calculation with ladder test obtained t count = 1.5 smaller than t table = 52 and decision making result that is: Ha accepted because t count t table (1,5 52) and Ho rejected because t count t table ( 1.5 52). The conclusion of the research shows that the media of color and shape shapes have a significant effect on the geometry understanding of group B children in TK Dharma Wanita Desa Bulukidul Kecamatan Balong Ponorogo.